Anti-chronic myeloid leukemia activity and quantitative structure-activity relationship of novel thiazole aminobenzamide derivatives. (15th July 2021) - Zhang, Yuan; Liu, Juan; Wu, Xin; Yang, Suming; Li, Yao; Liu, Songbin; Zhu, Saifei; Cao, Xuan; Xie, Zhizhong; Lei, Xiaoyong; Huang, Honglin; Peng, Junmei
Graphical abstract: Abstract: The anti-chronic myeloid leukemia activity of thiazole aminobenzamide derivatives in vitro was tested by a methanethiosulfonate (MTS)-based viability assay method, and the result showed that some compounds exhibited good inhibitory activities against human chronic myeloid leukemia cell line K562, imatinib-resistant strain K562/R and T135I mutant cell line BaF3 -ABL-BCR-T315I. Comparative molecular field analysis (CoMFA) and comparative molecular similarity index analysis (CoMSIA) methods were used to analyze the relationship between the structure of thiazole aminobenzamide derivatives and the inhibition of K562/R cell activity. In CoMFA, Q 2 was 0.899 and R 2 was 0.963; in CoMSIA, Q 2 and R 2 were 0.840 and 0.903, respectively. These data indicated that the selected test set showed suitable external predictive ability. Combined with the contour map results, we further analyzed the three-dimensional quantitative structure (3D-QSAR) model. The results demonstrated that in the backbone of the thiazole aminobenzamide derivative, the substitution of a small group at R 1 position, or the introduction of a hydrophilic group at R 2 position, or the introduction of a large-volume amino acid at R 3 position may be beneficial to improve the anti-CML activity of the compound.